Understanding Law and the Rule of Law: A Plea to Augment CS Curricula: Why law matters for computer scientists and other folk. - Hildebrandt, Mireille (Communications of the ACM, 2021)
The article draws parallels between legal ethics and computer science education. Ambiguity within computer systems is compared to the ambiguity of legal codification, the ability to disobey is presented as an essential characteristic of law, and the ethical limitations of the rule of law are outlined.